Lehre in Orthopädie und Unfallchirurgie = Teaching in orthopaedic and trauma surgery - Renkawitz, Tobias; Obertacke, Udo (Der Orthopäde, 2017)
The scramble for available places to study medicine in Germany continues. One of the core points within the “Master Plan 2020”, which has been recently adopted, is the reform of teaching concepts at German medical faculties. In the future, students of human medicine are to be trained primarily based upon competence-oriented, integrated curricula. The present paper is intended to present modern teaching concepts and methods, as well as current examination formats, which play a special role in student training in orthopaedics and traumatology. Knowledge in the field of medical and evidence-based treatment strategies, clinical examination techniques, diagnostic/therapeutic procedures and hygienic working conditions are especially important. Individual courses with a focus on research-, practice- and competence-orientation are intended to help the students grasp the depth of the subject.